Aberrent hepatic arteries, a rare anatomic variant: case report - Dhakal, Rajendra; Thakir, Binay; Shrestha, Shashank; Kharel, Ashis; Shah, Pankaj; Koirala, Bibhay Hari; Kandel, Shiva; Neupane, Deewas (Nepalese Journal of Cancer, 2023)
Anatomic variations of hepatic arteries are observed in 12-49% cases. But replaced right and left hepatic arteries are extremely rare (0.8%). We report a 61 years old male patient with the diagnosis of gastric cancer. He underwent distal subtotal gastrectomy with D2 lymphadenectomy. Intraoperatively, both right and left hepatic arteries were replaced and were arising from superior mesenteric artery and aorta, respectively.